Substantial impairment of voriconazole clearance by high-dose meropenem in a patient with renal failure - Mahmoudi, Mazyar; Brenner, Thorsten; Hatiboglu, Gencay; Burhenne, Jürgen; Weiß, Johanna; Weigand, Markus A.; Haefeli, Walter E. (Clinical infectious diseases, 2017)
Abstract. A critically ill patient with multiple postoperative infections repeatedly required profound voriconazole dose reductions whenever high-dose meropene
Gesehen am 10.08.2018